Cytotoxic activity and antioxidant effects of Origanum onites essential oil and its two major contents, carvacrol and p-cymene on human colorectal (HCT116) and hepatocelluler carcinoma (HepG2) cell lines - Becer, Eda; Altundag, Ergul Mutlu; Baser, K. Husnu Can; Vatansever, Hafize Seda (Taylor & Francis Inc, 2022)
Origanum onites L. (O. onites) is one of the cultivated Origanum species in Turkey. The aim of this study was to determine the cytotoxicity and cellular antioxidant effects of O. onites essential oil, carvacrol and p-cymene on HCT116 and HepG2 cells. O. onites essential oil components were analyzed by GC/MS and GC/FID. Cytotoxicity was analyzed via the MTT assay in HCT116 and HepG2 cells. Cellular antioxidant activities of O. onites essential oil, carvacrol and p-cymene were determined with DCFH-DA method. GC/MS analysis identified carvacrol (%78.4) as the main constituent of O. onites essential oil. 400 mu g/ml concentration of O. onites essential oil, carvacrol and p-cymene were found to be active against HCT116 and HepG2 cells. Also, carvacrol showed higher cellular antioxidant activity than O. onites essential oil and p-cymene. We conclude that O. onites essential oil and carvacrol may be a candidate for pharmaceutical products in treatment of cancer.
Keywords: Origanum onites L; essential oil; carvacrol; p-cymene; cancer; antioxidant